2023
DOI: 10.3389/fcogn.2023.1128442
|View full text |Cite
|
Sign up to set email alerts
|

Different oscillatory rhythms anticipate failures in executive and arousal vigilance

Abstract: IntroductionVigilance is the challenging ability to maintain attention during long periods. When performing prolonged tasks, vigilance failures are often observed, reflecting a decrease in performance. Previous research has shown that changes in oscillatory rhythms are associated with states of vigilance loss. The present study aimed to investigate whether changes in different oscillatory rhythms anticipate failures in two vigilance components: (a) executive vigilance –necessary to detect infrequent critical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…In short, while the executive vigilance decrement was associated with increased amplitude in late ERPs (i.e., P3 and SP), arousal vigilance loss was associated with reduced amplitude in early ERPs (i.e., N1 and P2). Importantly, the present outcomes further support different neural changes for executive and arousal vigilance (Luna et al, 2020; Luna et al, 2022) as part of attentional networks (Petersen & Posner, 2012; Posner & Petersen, 1990).…”
Section: Discussionsupporting
confidence: 75%
“…In short, while the executive vigilance decrement was associated with increased amplitude in late ERPs (i.e., P3 and SP), arousal vigilance loss was associated with reduced amplitude in early ERPs (i.e., N1 and P2). Importantly, the present outcomes further support different neural changes for executive and arousal vigilance (Luna et al, 2020; Luna et al, 2022) as part of attentional networks (Petersen & Posner, 2012; Posner & Petersen, 1990).…”
Section: Discussionsupporting
confidence: 75%
“…Vigilance was measured via the ANTI-Vea, a sensitive task that has proved to be effective in simultaneously measuring the decrement in two vigilance components (i.e., EV and AV) along with other attentional networks' functions in several lab and online behavioral studies (for a review, see Coll-Martín et al, 2023) as well as in psychophysiological research (Hemmerich et al, 2023;Huertas et al, 2019;Luna et al, 2023bLuna et al, , 2023aSanchis et al, 2020). Previous studies have shown acceptable reliability (i.e., Spearman-Brown splithalf correlations > .80) on the EV and AV scores of the ANTI-Vea, and at least a similar reliability on phasic alertness, orienting, and executive control scores as other versions of the ANT (Cásedas et al, 2022;Coll-Martin et al, 2021;Luna, Roca, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Dissociable patterns at the behavioral (Luna, Barttfeld, et al, 2022;Luna, Tortajada, et al, 2022;Román-Caballero et al, 2021), physiological (Feltmate et al, 2020;Sanchis et al, 2020;Sanchis-Navarro et al, 2024), and neural (Hemmerich et al, 2023(Hemmerich et al, , 2024Luna et al, 2020Luna et al, , 2023bLuna et al, , 2023a levels were observed for EV and AV when measuring vigilance components via the ANTI-Vea task. Most importantly, the EV and AV decrements were independently mitigated by stimulating different mechanisms of sustained attention.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, it has been proposed that vigilance can be considered as two dissociated components, which modulate different behavioral responses of sustained attention [7][8][9][10] . On the one hand, executive vigilance (EV) can be de ned as the ability to sustain attention for monitoring and detecting rare but critical events over an extended period.…”
Section: Introductionmentioning
confidence: 99%